Hubungan Antara Grit dan Regulasi Diri dalam Belajar terhadap Student Engagement pada Mahasiswa Penerima Beasiswa Penuh - Aisyah, Alifiana Rochmatul; Pramono, Ridwan Budi (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to determine the relationship between grit and self-regulation in learning to student engagement in students who receive full scholarships. The sampling technique used was purposive sampling, with a total of 100 active undergraduate students from 36 universities who received full scholarships. Data collection was carried out using three instruments, namely the student engagement scale, grit scale, and self-regulation scale in learning. The results of the analysis show that there is a highly significant positive relationship between grit and self-regulation in learning towards student engagement, with a correlation coefficient value of 0.817 and a significance value of p = 0.001 (p < 0.01), and an effective contribution of 66.8%. Based on these findings, the major hypothesis in this study is accepted. Further analysis showed that the grit variable had a highly significant positive relationship with student engagement, with a correlation coefficient of 0.754 and a significance value of p = 0.001 (p < 0.01), and an effective contribution of 56.8%. Thus, the first minor hypothesis is accepted. Meanwhile, the self-regulation variable in learning also showed a significant positive relationship with student engagement, with a correlation coefficient of 0.786 and a p value = 0.001 (p < 0.01), and an effective contribution of 61.8%. Therefore, the second minor hypothesis was also accepted. Overall, the results of this study indicate that both grit and self-regulation in learning have a significant relationship with the level of student engagement in full scholarship students.